Advocacy for gender minority students: recommendations for school counsellors. Issue 4 (4th July 2018) - Simons, Jack D.; Beck, Matthew J.; Asplund, Nancy R.; Chan, Christian D.; Byrd, Rebekah
Abstract: Research shows that teachers' and educators' responses to gender diversity issues in schools either improves or limits the experiences of students. The school counsellor has an important role to play in this process by working closely with other stakeholders to advocate for transgender, intersex and genderqueer (TIG) students. Following a review of recent developments in the USA, recommendations are made and resources identified to assist school counsellors in validating TIG students, and improving school systems in pursuit of their academic, social and emotional success.